SPAWNING BIOLOGY OF MYSTVS GULIO IN LAKE PULICAT, INDIA - Kaliyamurthy, M (Indian Journal of Fisheries, 2011)
Observations made on the length-weight relationship and some aspects of thespawning biology of Mystus gulio are gives. This species was observed to breedduring August-October in Lake Pulicat. The fecundity was found to vary from•1,283 to 24,768 in the fish of size range, 8